STELLA Facilitates Differentiation of Germ Cell and Endodermal Lineages of Human Embryonic Stem Cells - Wongtrakoongate, Patompon (Public Library of Science, 2013)
Stella is a developmentally regulated gene highly expressed in mouse embryonic stem (ES) cells and in primordial germ cells (PGCs). In human, the gene encoding the STELLA homologue lies on chromosome 12p, which is frequently amplified in long-term cultured human ES cells. However, the role played by STELLA in human ES cells has not been reported. In the present study, we show that during retinoic acid (RA)-induced differentiation of human ES cells, expression of STELLA follows that of VASA, a marker of germline differentiation. By contrast, human embryonal carcinoma cells express STELLA at a higher level compared with both karyotypically normal and abnormal human ES cell lines. We found that over-expression of STELLA does not interfere with maintenance of the stem cell state of human ES cells, but following retinoic acid induction it leads to up-regulation of germline- and endodermal-associated genes, whereas neural markers PAX6 and NEUROD1 are down-regulated. Further, STELLA over-expression facilitates the differentiation of human ES cells into BE12-positive cells, in which the expression of germline- and endodermal-associated genes is enriched, and suppresses differentiation of the neural lineage. Taken together, this finding suggests a role for STELLA in facilitating germline and endodermal differentiation of human ES cells.